Pengaruh Dukungan Sosial Orang Tua terhadap Perencanaan Karier Siswa - Salwa Azriyah; Muthahharah Thahir Thahir; Andre Julius (Ma'soem University, 2026)
This study aims to examine the influence of parental social support on career planning among 10th-grade students at SMA Mekar Arum. The study employs a quantitative inferential approach using simple linear regression analysis, with a saturated sample selection method. The subjects of this study are 10th-grade students at SMA Mekar Arum, with a total of 150 respondents. In this study, the research instruments used a parental social support scale with a reliability coefficient of 0.963 and a career planning scale with a reliability coefficient of 0.884. The results indicate a significant positive influence between parental social support and career planning, with a significance level of 0.000 < 0.05, with a coefficient of determination (R Square) of 0.384, indicating that parental social support influences the career planning of 10th-grade students at Mekar Arum High School by 38.4%. It can be concluded that if students receive social support from their parents, it will influence their career planning.